PEMBELAJARAN AKIDAH AKHLAK DI MTS YASRIB BATU-BATU KECAMATAN MARIORIAWA KABUPATEN SOPPENG (TINJAUAN FILSAFAT AKHLAK) - Asrina, Asrina; Nurbaety, Andi; Indah, Astrid Veranita (Aqidah-Ta: Jurnal Ilmu Aqidah, 2024)
This study aims to explore the forms of learning of aqidah and akhlak at MTs Yasrib Batu-Batu, Soppeng Regency. This study also analyzes the forms of learning of aqidah and akhlak at MTs Yasrib Batu-Batu, Soppeng Regency from the perspective of Moral Philosophy. This type of research is qualitative field research using the Theological, Phenomenological, and Philosophical Approaches. The stage of collecting research data begins with conducting observations, interviews and documentation. Data processing and data analysis techniques include data reduction, data presentation and deductive conclusion drawing. The results of the study show that the forms used in learning aqidah and akhlak at MTs Yasrib Batu-Batu are lectures, questions and answers, reading, listening and writing. With the combination of these forms of learning, it can improve understanding and application of moral values ​​and can help students apply teachings and deepen meaning and encourage critical thinking. In line with Al-Ghazali’s thoughts regarding the form of learning that focuses on holistic education, providing roles, examples, role models and practical experiences. Al-Ghazali also encouraged learning methods that involve practical experience and reflection so that students can apply moral values ​​in everyday life. This study has implications for the development of evaluation forms that not only measure cognitive knowledge, but also students’ attitudes and behaviors in applying moral values.